Satellite Image Mosaics Using Digital Cosine Transform (DCT) Descriptor - Abdul Jabar, H. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research work, a modified DCT descriptor are presented to mosaics the satellite images based on Abdul Kareem [1] similarity criterion are presented, new method which is proposed to speed up the mosaics process is presented. The results of applying the modified DCT descriptor are compared with the mosaics method using RMSE similarity criterion which prove that the modified DCT descriptor to be fast and accurate mosaics method.